(untitled) (Herald of Journalism, 2021)
The article examines the influence of the convergence process of the media in Almaty region on the Zhetysu TV channel. In addition, the achievements and goals of the Almaty regional TV channel «Zhetysu» with more than 20 years of history will be considered, as well as genre and program features of the TV channel will be considered. The purpose of this article is to analyze the possibilities of modern rapidly developing media. Modernization of the media space, analysis of their impact on today’s audience. The article examines the experience of media convergence on the example of the Almaty regional TV channel «Zhetysu», also takes into account the continuity of innovations and traditions. The research value of the topic is very relevant, since Zhetysu TV is the only TV channel located in Taldykorgan, the center of the Almaty region. The novelty of the study lies in the fact that for the first time convergence in the media was studied on the example of the Almaty regional TV channel «Zhetysu». The study examined the impact of information and technological processes on the audience, the impact of integration on changing the appearance of the media while maintaining the continuity of traditions in new media. The paper presents a detailed analysis of the work of the research object and recommendations. In addition, the development of the convergence process in the media was described and the features of integration processes in the domestic media space were studied. From a scientific and practical point of view, in accordance with modern requirements, the Zhetysu TV channel is a channel that provides comprehensive information using a variety of convergence opportunities. Research methods. The method of theoretical analysis was used in the work. Including the analysis of the convergence process, the analysis of various literature and articles, as well as the method of sorting statistical data. Key words. Media Сonvergence, Social networks, Zhetysu TV channel, rating programs, Traditional Media, New Media.